THE IMPACT OF MANAGEMENT CONTROL ON PUBLIC SECTOR ORGANIZATIONS IN INDONESIA - Maharani, Reny (UI Scholars Hub, 2021)
Using motivation crowding and self-determination theories, this study examines the relationship between elements of management control, intrinsic and extrinsic motivation, and the performance of public sector organizations in Indonesia. We used the Structural Equation Model (SEM) with a survey method on 187 employees of district/city governments in Indonesia to see if results, action, personnel, and cultural controls have an effect on employee motivation. Our study provides empirical evidence that motivation is influenced not only by results control, but also by other control elements such as action control and personnel control. This study also provides empirical evidence that intrinsic and extrinsic motivation can co-exist in improving organizational performance. This study contributes to the development of literature in the field of management accounting that shows the relationship between management control, employee motivation and organizational performance, as well as motivation as a mediator of the relationship between management control and organizational performance. The implications of this study include providing practitioners with information on which management control elements are most appropriate for enhancing employee motivation and performance in public sector organizations.